1992
DOI: 10.2134/jpa1992.0286
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Chemical Composition, and Ruminai Fermentability of Corn Whole Plant, Ear, andStover as Affected by Hybrid

Abstract: Total dry matter (DM) yield and grain content are commonly considered the most important factors forevaluating corn (Zea mays L.) hybrids for silage production with no considerationgiven to the nutritive value of the nongrain portion of the plant. Because the nongrain portion mayrepresent over 50% of the total DM in corn silage, we hypothesized that hybrid differences inchemical composition and ruminai fermentability of the stover portion of the plant may account forimportant nutritional differences in corn hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…In the present study, mean DMD ranged between 600 and 700 g kg −1 and mean NDFD between 500 and 550 g kg −1 of NDF, respectively. These mean values are consistent with the literature (from 450 to 700 g kg −1 for DMD, [9,32,33]; from 350 to 550 g kg −1 NDF for NDFD, [39,40]) and confirm that it is possible to achieve CS with high digestibility in Northern areas. The large range of digestibility reported in the literature is related to hybrid, planting date, environmental growing conditions, maturity at harvest, cutting height, and so forth.…”
Section: Yield Chemical Composition and Rumen Digestibilitysupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, mean DMD ranged between 600 and 700 g kg −1 and mean NDFD between 500 and 550 g kg −1 of NDF, respectively. These mean values are consistent with the literature (from 450 to 700 g kg −1 for DMD, [9,32,33]; from 350 to 550 g kg −1 NDF for NDFD, [39,40]) and confirm that it is possible to achieve CS with high digestibility in Northern areas. The large range of digestibility reported in the literature is related to hybrid, planting date, environmental growing conditions, maturity at harvest, cutting height, and so forth.…”
Section: Yield Chemical Composition and Rumen Digestibilitysupporting
confidence: 91%
“…In the present study, the mean NDF concentration (530 g kg −1 ) was greater than previously reported for CS (430 g kg −1 DM, 193,210 samples, [29]; 450 g kg −1 DM, [31]). Fiber concentration of CS typically declines with maturity due to dilution effects of increasing starch concentration [32,33]. Therefore, the greater mean NDF concentration is consistent with the lower mean starch concentration in this study (r = −0.71).…”
Section: Yield Chemical Composition and Rumen Digestibilitysupporting
confidence: 83%
“…Therefore, to increase digestibility of these lignocellulosic materials, it is important to destroy the linkage between cellulose, hemicellulose and lignin or destroy the compact nature of the tissue. There have been attempts to increase the nutritive values of the by-products by mechanical, chemical or biological treatments (McHan, 1986a;Iyo and Antai, 1988;Hunt et al, 1992;Singh et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Advancing maize crop maturity is associated with an increase in ear‐to‐stover ratio. These two plant components differ widely in their chemical composition and rumen fermentation characteristics (Hunt et al. , 1992) which suggests that the nutritive value of maize silage may change with crop maturity.…”
Section: Introductionmentioning
confidence: 99%